Effect of Artificial Nerve Conduit Vascularization on Peripheral Nerve in a Necrotic Bed. Issue 3 (March 2016) - Iijima, Yuki; Ajiki, Takashi; Murayama, Akira; Takeshita, Katsushi
Abstract : Background: Several types of artificial nerve conduit have been used for bridging peripheral nerve gaps as an alternative to autologous nerves. However, their efficacy in repairing nerve injuries accompanied by surrounding tissue damage remains unclear. We fabricated a novel nerve conduit vascularized by superficial inferior epigastric (SIE) vessels and evaluated whether it could promote axonal regeneration in a necrotic bed. Methods: A 15-mm nerve conduit was implanted beneath the SIE vessels in the groin of a rat to supply it with blood vessels 2 weeks before nerve reconstruction. We removed a 13-mm segment of the sciatic nerve and then pressed a heated iron against the dorsal thigh muscle to produce a burn. The defects were immediately repaired with an autograft (n = 10), nerve conduit graft (n = 8), or vascularized nerve conduit graft (n = 8). Recovery of motor function was examined for 18 weeks after surgery. The regenerated nerves were electrophysiologically and histologically evaluated. Results: The vascularity of the nerve conduit implanted beneath the SIE vessels was confirmed histologically 2 weeks after implantation. Between 14 and 18 weeks after surgery, motor function of the vascularized conduit group was significantly better than that of the nonvascularized conduit group. Electrophysiological and histological evaluations revealed that although the improvement did not reach the level of reinnervation achieved by an autograft, the vascularized nerve conduit improved axonal regeneration more than did the conduit alone. Conclusion: Vascularization of artificial nerve conduits accelerated peripheral nerve regeneration, but further research is required to improve the quality of nerve regeneration. Abstract : Supplemental Digital Content is available in the text.